Metode Baru Valuasi Ekonomi Dampak Langsung Spesies Asing Invasif Berbasis Kompetisi Makanan pada Ekosistem Perairan - Taryono Kodiran; Ali Mashar; Riska Febriana; Erin R Nurulhayati; Athifah Nurulhafidzah; Yusli Wardiatno (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Alien crayfish species (Cherax quadricarinatus and Procambarus clarkii) have been found in some Indonesian area and demonstrated invasive species characters. Despite of their economy benefit the crayfish has potential ecologically disadvantage to be valuated. This study aimed to develop valuation method to estimate economical loss due to alien invasive species on food competition basis in an aquatic ecosystem. This approach was conducted by estimating the potential loss due food competition between invasive species and its inferior competitor. The case study was carried out in the Lido Lake and in an aquaculture site at Cisaat, Sukabumi – West Java. The research results that economic loss due to the disappearance of native Macrobrachium sintangense caused by the existences of single male C. quadricarinatus is 784 IDR and 1,096 for the female in Lido Lake. The potential loss of M. rosenbergii due to the single P. clarkii is 1,416.76 IDR. The difference economic loss is constituted by the quantity of feed taken by the invasive species, and the economic value of competitive inferior species. This method is clearly explained in the method section and is simple to use, but more understandable for limited economics background stakeholders. However, this approach needs robust biological dynamic model. The valuation results become important reference for the policy maker to develop risk analysis in concern of introduced invasive species into an ecosystem. For holistic economic loss value valuation, further studies covering space competition and potential harmful pathogen carrier are warranted.